Pengembangan Multimedia Interaktif IPA Dengan Fitur Feedback Untuk Siswa Kelas VIII - Alfiansyah, Muhamad Firdaus; Adi, Eka Pramono; Soepriyanto, Yerry (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
The use of package book and student worksheet learning media made student bored quickly therefore they are lazy to follow the learning. The interactive media based learning with feedback feature can give motivation to the student, activating students in giving responses, feedback and encourage to do the right practices. The purpose of this development is to produce an interactive multimedia product with feedback feature natural science circulatory system material. The product is an application that can increase the motivation to learn and students’ interest during the learning process and make student easier to understand the human circulatory material. The research and development model used is the model by Lee and Owens. The result of media expert’s material, subject teachers and students is worth using, therefore it can be concluded that the interactive multimedia with feedback feature natural science human circulatory system material VIII grade has fulfilled the eligible criteria to be used in the learning activity.AbstrakPenggunaan media pembelajaran buku paket maupun LKS membuat pebelajar cepat bosan sehingga malas mengikuti pembelajaran. Pembelajaran berbasis multimedia interaktif dengan fitur feedback dapat memberikan motivasi kepada peserta didik, mengaktifkan peserta didik dalam memberikan tanggapan, umpan balik serta mendorong melakukan praktik-praktik yang benar. Tujuan pengembangan ini adalah menghasilkan sebuah produk multimedia interaktif dengan fitur feedback IPA msteri sistem peredaran darah. Produk berupa aplikasi yang dapat meningkatkan motivasi belajar dan ketertarikan pebelajar selama proses pembelajaran serta membuat pebelajar lebih mudah memahami materi peredaran darah manusia. Model penelitian dan pengembangan yang digunakan adalah model yang dikemukakan Lee dan Owens. Secara keseluruhan hasil tanggapan ahli media, ahli materi, guru mata pelajaran dan pebelajar dinyatakan layak maka dapat disimpulkan multimedia interaktif dengan fitur feedback IPA materi sistem peredaran darah manusia kelas VIII telah memenuhi kriteria layak digunakan dalam kegiatan pembelajaran.